Comparative efficacy of various art therapies for patients with dementia: A network meta-analysis of randomized controlled trials - Liu, Qian; Wang, Fang; Tan, Lixia; Liu, Li; Cheng, Hong; Hu, Xiuying (Frontiers in Psychiatry, 2023)
Background: Dementia have brought great challenges to patients, families and society. Numerous art therapies for patients with dementia have been developed in recent years. However, it is still unclear which art therapy represents the optimal strategy for promoting physical and mental health. Objectives: To compare the efficacy of various art therapies in improving cognitive function, activity of daily living, depression, anxiety, agitation behavior and quality of life, and rank the art therapies for practice consideration. Methods: A comprehensive literature search was performed in eight electronic databases from their inception to April 2022. Two authors independently completed study selection, data extraction, and assessed methodological quality according to the revised version of the Cochrane tool (RoB 2). Comparative evaluation of different art therapies’ effect was performed by conducting network meta-analysis. The study protocol was registered at PROSPERO. Results: 39 randomized controlled trials involving 2801 participants were included. Calligraphy therapy (MD = 4.39) and reminiscence therapy (MD =2.53) significantly improved cognitive function compared with the usual care, and reminiscence therapy (MD =1.75) significantly enhanced cognitive function compared with music therapy. Horticultural therapy significantly decreased agitation behavior compared with the usual care (MD =-31.34), music therapy (MD =-26.66), reading therapy (MD =-28.44) and reminiscence therapy (MD =-27.32). In addition, calligraphy therapy (MD =9.00) improved quality of life compared with the usual care. Conclusions: Calligraphy therapy might be the most effective art therapy for improving cognitive function and quality of life. Horticultural therapy might be the best art therapy for decreasing agitation behavior. Health-care professionals could consider applying these art therapies to improve cognitive function, agitation behavior and quality of life in patients with dementia.